2016
DOI: 10.1136/postgradmedj-2016-134159
|View full text |Cite
|
Sign up to set email alerts
|

The anticoagulation choices of internal medicine residents for stroke prevention in non-valvular atrial fibrillation

Abstract: Canadian internal medicine residents favoured warfarin over NOACs for patients with NVAF, which is in discordance with the evidence-based CCS guidelines. This finding persisted throughout the 3 years of core internal medicine training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…There existed no antidote for rivaroxaban or apixaban until the introduction of andexanet alfa in 2018-and still, no antidote has been recommended by a NICE technology appraisal. This is all in addition to potential inertia derived from prescriber preference and experience level [10]. Finally, a bevy of local factors such as pharmaceutical rebates, local incentives and policies, and patient demographics influence prescribing choices.…”
Section: Introductionmentioning
confidence: 99%
“…There existed no antidote for rivaroxaban or apixaban until the introduction of andexanet alfa in 2018-and still, no antidote has been recommended by a NICE technology appraisal. This is all in addition to potential inertia derived from prescriber preference and experience level [10]. Finally, a bevy of local factors such as pharmaceutical rebates, local incentives and policies, and patient demographics influence prescribing choices.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results about the importance of the patient's role have been reported also from other countries. In a Canadian survey for internal medicine residents, patient convenience was the second most important factor when choosing an OAC for patients with AF after adverse events . In Italy, 70% of internal medicine centres participating in a survey on DOACs regarded the patient's preference to be highly relevant when prescribing DOAC therapy in AF .…”
Section: Discussionmentioning
confidence: 99%
“…Shared decision‐making is considered appropriate for stroke prevention in AF because of the availability of several treatment options with different risk‐benefit profiles. Recent physician surveys and interviews suggest that physicians consider patient participation in decision‐making on the use of oral anticoagulants (OACs) in AF important . Physicians also report clinical characteristics of the patient, risk of adverse events, their own knowledge, experience and preferences to be important in decision‐making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated anticoagulation knowledge gaps in resident physicians. 11,12 One curriculum coauthor Irsk Anderson serves as the medical director for the Anticoagulant Management Service (AMS), an outpatient-based clinic that longitudinally follows and monitors patients on oral anticoagulation. Irsk Anderson, while serving as the AMS medical director as well as precepting the internal medicine residents in continuity clinic and on the inpatient wards, noted significant and concerning knowledge gaps within the residency program.…”
Section: Introductionmentioning
confidence: 99%